Parity-time symmetric chain resonators - Phang, Sendy; Vukovic, Ana; Creagh, Stephen; Gradoni, Gabriele; Sewell, Phillip; Benson, Trevor M. (2016)
A simple tight-binding model to study the band-structure of an infinite length Parity-time (PT) symmetric chain of resonators is presented in this paper. In the talk, we will investigate the impact of having a structure of finite length and consider the effect of a modulation of the real part of the refractive index on the complete band-structure of the PT-chain system. For a finite PT-chain structure under certain modulation, we observe the existence of a localised mode which is either lasing or dissipating